Review of Unlawful Acts of Livestock Owners Due to Crop Damage in Bombana Regency - Nurazizah, Nurazizah; Sari, Patma; Mayasari, Riezka Eka; Haerani, Yeni (Sangia Nibandera Law Research, 2024)
Regulation of unlawful acts Article 1368 of the Civil Code states that the owner of an animal or whoever uses it, as long as the animal is used, is responsible for the damage caused by the animal. Whether the animal is under his supervision or the animal gets lost or escapes his supervision. Responsibility of the owner of livestock due to damage to crops. shows that the responsibility of livestock owners towards plant owners is carried out by providing compensation to plant owners who suffer losses, using twonon-litigation settlement processes, namely, firstly negotiation, a bargaining process carried out by the parties to find a peaceful solution to the problem, secondly, the mediation process. settlement using a third party mediator. The type of research used by the author in the Normative Empirical research method is basically a combination of approaches between Normative law with the addition of Empirical elements.